Multi DGPV installation in transmission system for loss minimization - Mustaffa S.A.S.; Musirin I.; Othman M.M.; Rosli N.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer programming; Developing countries; Electric lines; Electric power transmission; Renewable energy resources; System stability; component; DGPV system; Generation expansion; Losses minimizations; Optimal placement and sizings; Power system networks; Renewable energy integrations; Transmission systems; Distributed computer systems